A Remote Operating Slit Lamp Microscope System - Tanabe, N.; Go, K.; Sakurada, Y.; Imasawa, M.; Mabuchi, F.; Chiba, T.; Abe, K.; Kashiwagi, K. (Methods of Information in Medicine, 2011)
Objectives: To develop a remote-operating slit lamp microscope system (the remote slit lamp) as the core for highly specialized ophthalmology diagnoses, and to compare the utility of this system with the conventional slit lamp microscope system (the conventional slit lamp) in making a diagnosis.Methods: The remote slit lamp system was developed. Three factors were evaluated in comparison to the conventional slit lamp. The ability to acquire skills was investigated using a task loading system among specialists and residents in ophthalmology. Participants repeated a task up to ten times and the time required for each task was analyzed. The consistency of the two systems in making a diagnosis was investigated using eyes of patients with ocular diseases as well as healthy volunteers.Results: The remote slit lamp is composed of a patient’s unit and ophthalmologist’s unit connected by high-speed internet. The two units share images acquired by the slit lamp in addition to the images and voices of patients and ophthalmologists. Both ophthalmology specialists and residents could minimize the completion times after several trials. The remote slit lamp took more time than the conventional slit lamp. Both systems showed a high consistency in evaluations among eyes with healthy eyes or those with ocular diseases.Conclusions: The remote slit lamp has a similar diagnostic ability, but required more examination time in comparison to the conventional slit lamp. The currently developed remote slit lamp has the potential to be employed for telemedicine purposes in the field of ophthalmology.
Keywords: Telemedicine; slit-lamp microscope; ophthalmology